2017
DOI: 10.1038/s41598-017-16062-5
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency backward four-wave mixing by quantum interference

Abstract: Electromagnetically-induced-transparency-based four-wave mixing (FWM) in a resonant four-level double-Λ system has a maximum conversion efficiency (CE) of 25% due to spontaneous emission. Herein, we demonstrate that spontaneous emission can be considerably suppressed by arranging the applied laser beams in a backward configuration. With the backward double-Λ FWM scheme, we observe a CE of 63% in cold rubidium atoms with an optical depth (OD) of 48. To the best of our knowledge, this is the first observation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…(25) and ( 26)]. This system is also known as an open-loop FWM system and can be used as an efficient frequency converter [40][41][42][43][44].…”
Section: Hadamard Gatesmentioning
confidence: 99%
“…(25) and ( 26)]. This system is also known as an open-loop FWM system and can be used as an efficient frequency converter [40][41][42][43][44].…”
Section: Hadamard Gatesmentioning
confidence: 99%
“…The suppression and enhancement of four-wave-mixing (FWM) process in electromagnetically induced transparency (EIT) windows [1][2][3][4][5][6][7][8] can be implemented in many multi-level systems, such as ladder-type, [2,9,10] Y-type, [8] and double lambda-type [4][5][6][11][12][13] level configurations. In a ladder-type system with hyperfine ground states, the magnitude of FWM signal is found to be dependent on the transition route, and dominantly related to the residual two-photon coherence according to the degree of optical pumping to the other ground state.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Recently, in a backward double-lambda system, the conversion efficient in cold rubidium atoms was observed to be 63%, and the conversion efficient was predicted to be 96% by using a medium with a large optical depth. [13] The control of FWM process can be achieved by changing several parameters of the fields applied to the system, e.g., the detuning and the strengths, [8,14] the relative phases, [15] and the pulse dynamics. [16] This control of FWM process can be applied to the quantum entanglement, [17] the fabrication of scalable multimode quantum resources, [18] and the enhancement of bright-seeded SU (1,1) interferometer.…”
Section: Introductionmentioning
confidence: 99%
“…While current work towards CPC uses nonlinear waveguides and is limited by the efficiency of the quantum process [22], atomic systems can create FWM [23] at near unitary efficiencies, and are an excellent candidate for highly efficient CPC. Additionally it has been shown that with these same FWM systems, it is possible to achieve large XPM at the low light level without requiring cavities, storage or Rydberg levels through a double-Λ system [24].…”
Section: Introductionmentioning
confidence: 99%